PERANCANGAN SISTEM RESERVASI KAMAR HOTEL BERBASIS WEB DENGAN PEMODELAN UML - Aisyah Rahma Setiaputri; Alvita Dita Azzahra; Lathisya Sheza Aldamar; Zatin Niqotaini (CV. Denasya Smart Publisher, 2025)
Hotel is one of the service sectors that provides lodging services for the community. In its operations, there are currently several hotels that still carry out the reservation process manually, such as ordering by telephone and recording guest data conventionally. This can hamper service efficiency and accuracy. This research intends to design a web-based hotel room reservation system that can digitize the booking and room management process. The method includes needs analysis, literature study, system analysis, system design with Unified Modeling Language (UML) model, interface mockup, testing, and implementation. The innovations developed include online room reservation features, room data management, and reporting systems. The system was designed using various Unified Modeling Language (UML) diagrams such as use case diagram, activity diagram, sequence diagram, and class diagram, along with user interface (UI) design. This research is expected to play an important role in increasing the efficiency of hotel operations, making it easier for customers to make reservations, and minimizing errors in recording booking data.